Changes in inequality within countries after 1990 - Carlos Gradín (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
In this paper, we use the World Income Inequality Database to assess the main trends in inequality within countries since around 1990. We cope with the heterogeneity in the original information (regarding the measure of resources, equivalence scale, etc.) by focusing on the trends rather than on the levels, and by comparing like to like within countries. With only a few exceptions, we compare the same inequality concept obtained from the same source in two different years in each country, even if the concept and source will differ across countries. The results show that there was a majority of countries witnessing a decline of inequality as measured by the Gini index, even if once accounted for the fact that inequality increased in the most populous countries, it turns out that a majority of people saw inequality increase in their country over this period of time. These trends are complemented with information for inequality in income and wealth from other sources, paying special attention to the top of the distribution.
Keywords: D63; I31; O5; 330; inequality; income; Gini; WIID